Isolation and characterization of diphenyl ether degrading bacterium Sphingomonas sp. DZ-3 - Feng Zhuo; Wang Sheng; Bai Naling; Zhao Yuhua (浙江大学学报. 农业与生命科学版, 2015)
Polybrominated diphenyl ethers (PBDEs) are man-made flame-retardant chemicals that are widely used to decrease the flammability of plastics, electronic appliances, textiles and polyurethanes. Annually, more than 67 400 tons of PBDEs including penta-, octa-, and deca-BDE were produced. PBDEs can be incorporated into polymers without any covalent bonds to adjacent materials. Because of the widespread production and improper disposal of these polymers, PBDEs have been accumulated in the environment. The toxicity of PBDEs is variable for different congeners. Some of them show neurotoxic toxicity in mice and dioxin-like endocrine disruption. In spite of the accumulation of PBDEs in the environment, few remediation technologies have been investigated sufficiently. A few works of biological degradation of PBDEs have been done in recent years.An efficient diphenyl ether degrading bacterium strain DZ-3, which was able to utilize diphenyl ether as a sole source of carbon and energy under aerobic condition, was isolated from activated sludge of a wastewater treatment plant. The growth and degradation character of the strain were studied in order to offer some useful informations for the remediation of contamination.In addition to the diphenyl ether degrading bacterium DZ-3, the other bacterium strain CZ-3 was also isolated, which can't degrade biphenyl ether. But the mixed cultures of the two strains could enhance the degradation of diphenyl ether compared with DZ-3 cultivation. Based on 16S rDNA gene sequencing, the strains DZ-3 and CZ-3 were identified as Sphingomonas sp. DZ-3 and Ochrobactrum sp. CZ-3. Mixture design was used to adjust the proportion of each strain and the optimal ratio of inoculation size was DZ-3∶CZ-3=2∶3. Diphenyl ether degradation experiments using high performance liquid chromatograph (HPLC) showed that the strain DZ-3 could degrade 71% of diphenyl ether (initial concentration of 835 mg/L) within 6 days, while the mixture of DZ-3 and CZ-3 could degrade 90% within 4 days. To further investigate the degree of metal ions affecting the biodegradation of Sphingomonas sp. DZ-3, a background propagation artificial neural network (ANN) was used to conduct a sensitive analysis on the individual variables. The ANN model showed satisfactory fits for the experimental data. The results indicated that Mg2+ appeared to be the most important metal ion for the biodegradation of DZ-3 with a relative importance of 31.01%, followed by Co2+(25.45%), Ni2+(15.12%), in which Mg2+ had a positive effect on the degradation, while Co2+ and Ni2+ had negative ones. In addition, the strain DZ-3 even catabolized biphenyl and monobrominated diphenyl ether. Meanwhile, the degradation of biphenyl ether in the polluted soil added with the exterior microorganism was studied by lab simulation. In lab simulation, the degradation percentage of diphenyl ether by Ochrobactrum sp. CZ-3 and Sphingomonas sp. DZ-3 was 71% within 3 days and 98% within 6 days. The degradation effect was significant, indicating that the mixed culture had great potential for remediation of contaminated soil.In conclusion, the research on the characteristics of the diphenyl ether biodegradation can provide theoritical basis and experience about engineering application for bioremediation of diphenyl ether and PBDEs polluted sites.